Predictors and enablers of mental health nurses' family‐focused practice. (27th June 2018) - Grant, Anne; Reupert, Andrea; Maybery, Darryl; Goodyear, Melinda
Abstract: Family‐focused practice improves outcomes for families where parents have a mental illness. However, there is limited understanding regarding the factors that predict and enable these practices. This study aimed to identify factors that predict and enable mental health nurses' family‐focused practice. A sequential mixed methods design was used. A total of 343 mental health nurses, practicing in 12 mental health services (in acute inpatient and community settings), throughout Ireland completed the Family Focused Mental Health Practice Questionnaire, measuring family‐focused behaviours and other factors that impact family‐focused activities. Hierarchical multiple regression identified 14 predictors of family‐focused practice. The most important predictors noted were nurses' skill and knowledge, own parenting experience, and work setting (i.e. community). Fourteen nurses, who achieved high scores on the questionnaire, subsequently participated in semistructured interviews to elaborate on enablers of family‐focused practice. Participants described drawing on their parenting experiences to normalize parenting challenges, encouraging service users to disclose parenting concerns, and promoting trust. The opportunity to visit a service user's home allowed them to observe how the parent was coping and forge a close relationship with them. Nurses' personal characteristics and work setting are key factors in determining family‐focused practice. This study extends current research by clearly highlighting predictors of family‐focused practice and reporting how various enablers promoted family‐focused practice. The capacity of nurses to support families has training, organizational and policy implications within adult mental health services in Ireland and elsewhere.